Integrasi Nilai Islami dan Kearifan Lokal dalam Modul Digital Kepemimpinan untuk Meningkatkan Kinerja Guru SMA - Jakiyah, Paridah; Rahman, Novianti Azizah; Pamela, Karim (LPPM Institut Pendidikan Nusantara Global, 2025)
Various facts in the field, supported by empirical findings, indicate that not all school principals have an adequate understanding of the essence, quality, and function of educational leadership, which has implications for suboptimal teacher performance. Therefore, innovation in developing principals' leadership styles is urgently needed to shape leaders with noble character and able to motivate teacher performance. Teachers are valuable school assets, and maintaining their performance is a crucial task for principals to create a conducive learning environment. An approach based on Islamic values (such as amanah and ihsan) and local wisdom offers a solution to forming leaders with integrity and contextualization. The purpose of this study is to develop and test the effectiveness of a digital leadership module based on Islamic values and local wisdom as a strategic effort to improve high school teacher performance. This research is a research and development (R&D) using the ADDIE method. A digital module was developed and implemented with 50 school principals in Majalengka, West Java. The effectiveness of the module was measured through a quantitative pre-test and post-test approach on the performance of 500 teachers in 50 related high schools/Islamic senior high schools. The results showed a statistically significant increase in teacher performance after the module implementation. The average increase in overall teacher performance reached 25% (Pre-Test Score: 69.05 to Post-Test Score: 86.25) with a significance value (P < 0.01). The highest increase occurred in the Character and Work Ethics dimension (27.5%). This finding indicates that principal leadership based on Islamic principles (amanah and ihsan) is able to build trust and respect, which crucially impacts teacher performance improvement. Therefore, this module has proven to be very feasible and effective as a guide to improving principal leadership competency.